Leadership and Crisis Communication During Covid-19: The Case of Brunei Darussalam - Li Li Pang (Policy & Governance Review, 2021)
National leaders’ responses to the Covid-19 pandemic globally have shown that while the definition of leadership is still debatable in academia, in times of crisis, it is easily identifiable and seen. The world has seen different responses by national leaders to curb the spread of the virus, Covid-19, which has claimed more than a million lives, affecting 189 countries worldwide since January 2020. Developed countries’ successes in dealing with the pandemic are widely reported by international media, but the successes made by developing countries are not. One such country is Brunei Darussalam, where her success, even regionally in Southeast Asia, was downplayed. This paper is a qualitative case study, highlighting Brunei Darussalam’s success in handling the pandemic. Brunei Darussalam began to ‘flatten the curve’ since March 29, 2020 and there was no local transmission since May 7, 2020. The paper will show how leadership, effective crisis communication together with advances in telecommunication technologies, existing institutional practices, and a supportive public have helped Brunei Darussalam curb the spread of the virus within the country.